New Results in Optical Modelling of Quantum Well Solar Cells - Silvian Fara; Paul Sterian; Laurentiu Fara; Mihai Iancu; Andreea Sterian (International Journal of Photoenergy)
This project brought further advancements to the quantum well solar cell concept proposed by Keith Barnham. In this paper, the optical modelling of MQW solar cells was analyzed and we focussed on the following topics: (i) simulation of the refraction index and the reflectance, (ii) simulation of the absorption coefficient, (iii) simulation of the quantum efficiency for the absorption process, (iv) discussion and modelling of the quantum confinement effect, and (v) evaluation of datasheet parameters of the MQW cell.